The effects of variable mechanical parameters on peak power and energy consumption of ankle-foot prostheses at different speeds. (2nd December 2018) - Dong, Dianbiao; Convens, Bryan; Sun, Yuanxi; Ge, Wenjie; Cherelle, Pierre; Vanderborght, Bram
ABSTRACT: In recent years, powered ankle-foot prostheses are developed to restore human ankle behaviour. Compared with common passive ankle prostheses, a powered ankle-foot prosthesis can provide amputees with better performance on walking gait by providing additional energy. However, the electrical peak power of powered ankle-foot prostheses at high speed is still a big challenge for the current actuation system. While most researchers focus on the energy consumption on one walking speed, we investigate the influences of several variable mechanical parameters to reduce electrical peak power during different locomotion speeds. Then we apply this concept to current ankle-foot models. It's found that the variable mechanical parameters can significantly reduce the demand of electrical peak power at different speeds. Meanwhile, the reduction of the electrical peak power does not lead to a large increment of the energy consumption. The results also show that every variable mechanical parameter has a different influence on the peak power and energy consumption of the ankle-foot prosthesis. It means the most effective and sensitive variable mechanical parameter need to be found for a specific ankle prosthesis system. GRAPHICAL ABSTRACT: